Relative contributions of upper-body muscular power and repeated sprint ability to 50-m freestyle swimming performance in competitive swimmers - Amara, S.; Bouassida, A.; van den Tillaar, R. (Frontiers in Sports and Active Living, 2025)
Upper-body muscular power and repeated sprint ability are recognized as important contributors to sprint swimming performance. However, the relative and combined predictive value of dry-land power measures and in-water repeated sprint ability for 50-m freestyle performance remains insufficiently understood. This study aimed to examine the relationships between upper-body muscular power, repeated sprint swimming variables (RSS), and 50-m freestyle performance in competitive swimmers. Thirty-six national-level male swimmers (age: 16.4 ± 0.3 years) participated in this cross-sectional study. Each swimmer completed: (1) an upper-body load-velocity assessment using the bench press on a Smith machine equipped with a linear position transducer to determine peak power; (2) an in-water repeated sprint test (8 × 15 m, 30 s rest) to determine fastest time, mean time, fatigue index, and total time; and (3) a maximal 50-m freestyle time trial. Pearson correlations revealed a very strong negative relationship between maximum muscular power and 50-m time (r = -0.86, p < 0.001), indicating that higher power was associated with faster swim performance. Among the RSS variables, fastest time (r = 0.83, p < 0.001), mean time (r = 0.78, p < 0.001), and total time (r = 0.78, p < 0.001) showed significant positive correlations with 50-m time, while fatigue index was not significantly related (r = 0.05, p = 0.78). The multiple regression model significantly predicted 50-m performance (R² = 0.86, p < 0.001), but only maximum muscular power emerged as an independent significant predictor (ß = -0.027, p < 0.001). Upper-body muscular power was the strongest determinant of 50-m freestyle performance, explaining most of the variance in sprint time, while repeated sprint swimming variables reflect related in-water expressions of sprint capacity. Coaches should prioritize the development of dry-land power capacity alongside in-water anaerobic conditioning to enhance sprint performance. Combining load-velocity profiling and repeated sprint testing offers a complementary and practical framework for performance monitoring and individualized training prescription in competitive swimmers.